The Influence of Company Characteristics and Foreign Ownership on Sustainability Report Disclosure in LQ45 Companies Listed on the Indonesia Stock Exchange - Christin Natalia Sitompul; Meliana Puspitasari; Awaliawati Rachpriliani (STIE Amkop Makassar, 2026)
The study examined how company size, profitability, debt levels, age, and foreign ownership influence how companies report sustainability issues. The study sampled 32 corporations listed on the LQ45 index in the Indonesian capital market from 2020 to 2024, using a purposive sampling technique . The study's findings indicate that company size, debt ratio, and length of existence do not significantly impact sustainability reporting. However, profitability and foreign ownership are significantly influential. The study indicates that a company's profitability and participation from foreign investors can lead to increased corporate transparency through disclosure of sustainability-related information. This study supports all stakeholders in evaluating a company's commitment to sustainability practices based on published information.